INFLUENCE OF WEATHER PARAMETERS ON SUCROSE ACCUMULATION IN SUGARCANE (SACCHARUM OFFICINARUM L.) - D, ADILAKSHMI (The Journal of Research ANGRAU, 2026)
The ripening of sugarcane is largely influenced by weather factors such as sunlight,temperature, and rainfall. This study evaluated ten sugarcane clones over two crop years (202324 and 2024–25) under the agro-climatic conditions of Andhra Pradesh, India, to assess theeffect of weather parameters on sucrose accumulation. The clones were observed from Octoberto February and data on sucrose percentage and weather elements (maximum and minimumtemperature, rainfall, and bright sunshine hours (BSSH)) were collected. Correlation analysisrevealed that BSSH had a strong positive correlation (r = 0.75) with mean sucrose, followed byminimum temperature (r = 0.54), while rainfall showed a negative correlation (r = –0.68). Theseresults affirm the critical role of incident sunlight and cold weather in enhancing ripening. Clones2022A 93, 2022A 203, and 2022A 88 demonstrated superior performance across seasons andcan be considered for further line development or trait introgression breeding.